Artistic Enhancement. Literature and Film as Mirror and Means of Human Enhancement - Fürholzer, Katharina (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2018)
Human enhancement affects all members of society and is thus closely linked to issues of social justice: up to now, the promises and perils of enhancement are usually only known to, and thus used, by few members of society. This can lead to individual competitive advantages that create or widen social gaps. Broad public information is, therefore, key to ensure that enhancement does not conflict with the principle of equality of opportunities. As possible means of public information, literature and films are able to counter such possible social injustice, which is why they may be allotted a central role in the ethical debates on human enhancement. Two aspects will be considered in this regard: 1) enhancement in art and 2) through art. 1) The extent to which artistic depictions and public information and perceptions of enhancement may be intertwined will be illustrated by two examples where both texts and their accompanying paratexts had a particular bearing on the public debate on enhancement: the film Gattaca of 1997 and the novel Never let me go (2005) by Nobel laureate Kazuo Ishiguro. 2) The second part of the paper is dedicated to the question of how far enhancing selected groups of society may contribute to a greater common good and which potentials art can offer in this regard. Three groups of persons will be taken into account: 1) clinical ethics committees, 2) physicians, and 3) patients.